Leverage, Growth Opportunity Dan Investasi Pada Perusahaan Non Keuangan Yang Terdaftar Di BEI - Andri Rianawati; Rahmat Setiawan (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2015)
Company's investment activities in Indonesia experienced significant fluctuations. Companies make the investments in order to enhance shareholder value. In connection with investment decision-making, company should consider the internal conditions, such as the condition of the company's bank debt or leverage conditions. Moreover, before making an investment decision, the company should consider the investment opportunities (growth opportunity). This study aims to identify the effect of leverage on investment and whether a company that has low growth opportunity has lower investment. This is seen by adding moderating variable-growth opportunity in leverage effect on investment, which is proxied by Tobin's Q and sales growth. The samples used were non-financial companies listed on the Indonesia Stock Exchange in 2009 through 2013. The regression results showed significant negative effect of leverage on investment. This means that the leverage gives a negative impact on investment, the higher the leverage makes the investment lower. This happens because the bank debt raises investment restrictions on companies, thus higher bank debt will strengthen the restrictions on the investments made by the bank. Moderation model, of growth opportunity proxied by Tobin's Q and Sales Growth, weakens the negative effect of leverage on investments in companies with low growth opportunity. This means, companies with low growth opportunities has weaker negative influence of leverage on the investment. This is because, companies that have low growth opportunity, have a lower profitable investment projects, so restrictions on investments made by the bank or keditor are looser.